Peningkatan Kualitas Mutu Minyak Pliek U Dengan Penambahan Campuran Minyak Kayu Manis Dan Minyak Serai Wangi - Maghfirah, Maghfirah; Faridah, Faridah; Sari, Ratna (Politeknik Negeri Lhokseumawe, 2022)
The process of making pliek u is a traditional Acehnese food made from fermented coconut flesh. There are by-products, namely simplah oil and brok oil. Simplah oil is pliek u oil that is produced without going through the drying process in the sun. The purpose of this study was to remove the rancid odor of pliek u oil with the addition of cinnamon and citronella oil so as to reduce water content, free fatty acids and peroxide numbers. The stages of the research process include the mixing and soaking process. The process of mixing pliek u oil at a temperature of 90 C for 15 minutes by varying the concentration of cinnamon oil and citronella oil 5;0, 0;5, 5;2,5, 2,5;2,5, 5;5 and then it will be carried out immersion for 10, 20, 30, 40, 50 days. The results showed that the highest water content on the 50th day was 0.0733% and the lowest on the 10th day was 0.0033% while the best peroxide value was the ratio of 5:5 which tended to meet SNI but was not optimal. the best free fatty acids on day 30 and the optimum ratio in overcoming rancidity in pliek u oil was 4.67%. As for the organoleptic test (smell and color) the most preferred was on the 30th day with a ratio of 5;2.5